AXHg3P2S8 (A = Rb, Cs; X = Cl, Br): New Excellent Infrared Nonlinear Optical Materials with Mixed‐Anion Chalcohalide Groups of Trigonal Planar [HgS2X]3− and Tetrahedral [HgS3X]5−. Issue 15 (20th May 2021) - Xing, Wenhao; Tang, Chunlan; Wang, Naizheng; Li, Chunxiao; Uykur, Ece; Wu, Jieyun; Lin, Zheshuai; Yao, Jiyong; Yin, Wenlong; Kang, Bin
Abstract: A series of nonlinear optical (NLO) chalcohalides AXHg3 P2 S8 (A = Rb, Cs; X = Cl, Br), which contain various Hg‐based building units including mixed‐anion trigonal planar [HgS2 X] 3− and tetrahedral [HgS3 X] 5−, are successfully synthesized. These compounds display good water resistance, wide infrared transparent region (0.42–17 µ m), high laser‐induced damage thresholds (4.5–6 × AgGaS2 ), and strong phase‐matchable second harmonic generation (SHG) response close to AgGaS2 . The mixed‐anion chalcohalide groups serving as functional building units in NLO materials are studied for the first time and proven to be very effective. This work opens a new avenue for new NLO material design to achieve the balance between strong SHG efficiency and large bandgap. Abstract : New mixed‐anion chalcohalide groups trigonal planar [HgS2 X] 3− and tetrahedral [HgS3 X] 5− are successfully constructed and serve as functional building units in AXHg3 P2 S8 (A = Rb, Cs; X = Cl, Br) compounds, which display an excellent overall ​ infrared nonlinear optical performance including good water resistance, wide infrared transparent region, high laser‐induced damage thresholds, and strong phase‐matchable second harmonic generation response.